Cardiovascular changes associated with infusion of hematopoietic cell grafts in oncohematological patients — impact of cryopreservation with dimethylsulfoxide - Horacek, J.M.; Jebavy, L.; Jakl, M.; Zak, P.; Mericka, P.; Maly, J. (Experimental Oncology, 2009)
Aim: Dimethylsulfoxide (DMSO) is the most frequently used agent for hematopoietic cell (HC) graft cryopreservation. This study aimed to monitor blood pressure and heart rate (HR) during HC graft infusion and assess the impact of cryopreservation with DMSO. Methods: 153 HC graft infusions in 153 consecutive hematological patients (mean age 49.1 ± 12.6 years; 80 males) were evaluated. Cryopreservation with DMSO was used in 133 grafts (DMSO group). Twenty grafts were infused directly without cryopreservation (control group). Systolic blood pressure (SBP), diastolic blood pressure (DBP) and HR were measured immediately before and after HC graft infusion. Results: SBP and DBP increased significantly after graft infusions cryopreserved with DMSO (p < 0.0001 for SBP; p < 0.01 for DBP). Increases (> 10 mmHg) in SBP were seen in 42 (31.6%) patients; in DBP in 31 (23.3%) patients. Changes in HR were non-significant in DMSO group. Increases in BP and HR correlated with increasing DMSO dose (p < 0.01; p < 0.05, respectively). Changes in SBP, DBP and HR were non-significant in control group. Conclusion: HC graft infusions cryopreserved with DMSO could cause statistically significant increases in SBP and DBP, without changes in HR. These changes were mostly transient and asymptomatic, not requiring therapeutic intervention. However, they might cause complications, especially in patients with preexisting cardiovascular disease, who should be monitored closely during HC transplantation.